“Small axonless neurons”: postnatally generated neocortical interneurons with delayed functional maturation - Le Magueresse, Corentin; Alfonso, Julieta; Khodosevich, Konstantin; Martín, Ángel A. Arroyo; Bark, Christine; Monyer, Hannah (The journal of neuroscience, 2011)
GABAergic interneurons of the mouse cortex are generated embryonically in the ventral telencephalon. Recent evidence, however, indicated that a subset of cortical cells expressing interneuronal markers originate in the neonatal subventricular zone. This has raised interest in the functional development and incorporation of these postnatally generated cells into cortical circuits. Here we demonstrate that these cells integrate in the cortex, and that they constitute two distinct GABAergic interneuronal classes. Whereas one class reflects the tail end of embryonic interneuron genesis, the other class comprises interneurons that are exclusively generated perinatally and postnatally. The latter constitute a novel subclass of interneurons. They are preferentially located in the deeper layers of the olfactory and orbital cortices, exhibit a unique firing pattern and slow functional maturation. Based on their distinct morphology we termed them “small axonless neurons” and indeed, unlike other cortical neurons, they communicate with their neuronal partners via dendrodendritic synapses. Finally, we provide evidence that the number of small axonless neurons is enhanced by odor enrichment, a further indication that they integrate into neural circuits and participate to olfactory processing.